Shock Fitting : Classical Techniques, Recent Developments, and Me moirs of Gino Moretti - Onofri, Marcello; Paciorri, Renato (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes the revolutionary capabilities of new shock fitt ing algorithms; a great improvement in computational fluid dynamics (CF D) for high-speed numerical simulations. Shock fitting methods provide a solution to the current difficulties and inaccuracies in shock-captur ing approaches. This work traces the evolution of shock-fitting methods , from the pioneering methods based on the structured grids (boundary a nd floating shock-fitting) to recent developments on unstructured grids , illustrating algorithmic details, significant applications and potent ial developments. Also, to celebrate the centenary birth of the father of shock-fitting techniques, the book also includes a tribute to Gino Moretti, as well as his unpublished manuscript. This book will appeal t o professionals, researchers, and graduate students in the field of CFD .
Part1. Floating Shock-Fitting -- Chapter6. Shock-Fitting Analysis -- Chapter7. Steady and Unsteady Shock Interactions by Shock Fitting Appr oach -- Part2. Recent Developments in Shock-Fitting Techniques for Unst ructured Grids -- Chapter8. Basic Elements of Unstructured Shock-Fittin g: Results Achieved and Future Developments -- Chapter9. SF: an Open So urce Object-Oriented Platform for Unstructured Shock-Fitting Methods -- Chapter10. Shock-Fitting and Predictor-Corrector Explicit ALE Residual Distribution -- Chapter11. A Shock-Fitting Technique for ALE Finite Vo lume Methods on Unstructured Dynamic Meshes -- Chapter12. Inserting a S hock Surface into An Existing Unstructured Mesh -- Chapter13. ShockWave Detection Based on the Theory of Characteristics. Part1: Tributo to Gi no Moretti -- Chapter1. Gino Moretti: a Man for all Seasons -- Chapter2 . A Renaissance Man: Personality and Generosity of a Dear Friend -- Cha pter3. Gino Moretti at GASL, Brooklyn Poly, and the Later Years -- Chap ter4. Gino Moretti, the Maestro of Gas Dynamics -- Chapter5. ThereWas a Conference in Europe.
Description based on publisher-supplied MARC data.
Keywords: Applied mathematics; Engineering mathematics; Fluid mechanics; Fluids; Physics; Fluid- and Aerodynamics; Engineering Fluid Dynamics; Mathematical and Computational Engineering; Numerical and Computational Physics, Simulation